FEATURES OF THE INFLUENCE OF PHYSICAL LOADS OF DIFFERENT DIRECTIONS ON THE PERFORMANCE INDICATORS OF FEMALE STUDENTS OF DIFFERENT SOMATOTYPES - Levushkin, S.P.; Fesenko, M.S.; Li Xun; Solovieva, E.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the features of the influence of physical loads of various directions on the physical fitness of female students of different somatotypes.Results and conclusions. Within the framework of this work, the features of the influence of loads of various sports orientations on the physical fitness of female students of different somatotypes are determined.The pilot study involved female students involved in volleyball, basketball, swimming and fitness as part of elective physical education courses. All participants in the experiment were identified body type: asthenic, thoracic, muscular and digestive. For a comparative assessment of physical performance under the influence of loads of different sports directions, the following methods were used: functional test PWC170 and determination of the magnitude of the intensity of accumulation of pulse debt (IAPD).